Glucose-6-Phosphate Dehydrogenase Status in the Term Newborns and Their Clinical and Other Laboratory Correlates - Dey, Sanjoy Kumer; Jahan, Ismat; Mkh, Shabuj; Shaha, Chandan Kumar; Chowdhury, Suparna; Naznin, Lubna; Rahman, Kazi Monisur; M, Shahidullah (Bangladesh Journal of Child Health, 2020)
Background: Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most common enzyme defect in man. Though G6PD deficiency affects every cell in the body, its primary effects are hematological. Objectives: The objectives of the study were to determine the G6PD enzyme concentration and deficiency states among the term newborns, to see the impact of the enzyme status with development of neonatal jaundice and to delineate any correlation of the G6PD with other hematological values. Materials and Method: Total 100 term newborns were enrolled in the study. Umbilical cord blood sample from the placental end were collected for G6PD enzyme assay, blood counts including reticulocyte count, blood indices and bilirubin estimation. Clinical and other relevant data were collected. Statistical analysis was done by using SPSS 19.0 version. Results: Overall G6PD activity was detected 9.86 ± 1.68 U/g Hb and no G6PD enzyme deficiency state was identified. There were no statistically significant differences in the hematological parameters and cord blood bilirubin concentration between male and females. But females have significantly higher G6PD enzyme concentration than males (p=0.002). There were no significant differences in the enzyme concentration in different gestational age groups. There was significant negative correlation between G6PD enzyme and hemoglobin levels, G6PD enzyme concentration with HCT and MCV values. Conclusion: This study could not identify any G6PD deficiency state. So further large scale community-based study is needed to validate this finding and also establish the normal G6PD enzyme concentration in the population of Bangladesh. Bangladesh J Child Health 2020; VOL 44 (1) :18-23